Diseño y construcción de un generador eléctrico de desplazamiento lineal con imanes permanentes para acoplamiento a un aerogenerador de eje vertical. - Quichimbo Armijos, Juan Carlos (2013)
The development of new models of electrical generation has been enormous in the last years due to the great variety of uses to which vehicles are submitted, as auto sustainable houses, pumping, etc. At present, there exists the trend to diminish the cost and the size of these electrical generators, as consequence of the intensive development of the technology for the manufacture of these machines. Nevertheless, the generators commonly use the rotating movement, it he performs for it our effort in the investigation to take advantage of the alternative movement for electrical generation. In this work, one proposes the location of the magnets and of the wound one of agreement to the best result of the tests in the different prototypes with which it was experienced. The circuit proposes wave rectifier itself to turn the alternate tension in constant and to be able to store the energy in a battery, then with an investor it the transforms again to a sinusoidal wave and to be able like that to install normal load. An offer is described to locate the wound one with nucleus of iron, the way of locating the permanent magnets of neodymium to stop to generate the magnetic field, the magnets are located alternadamente to obtain the variation of voltage, and the necessary adjustments are realized in order that they are the magnets who do the alternative movement. Installed twelve bobbins with which it he counts the generator there is recommended also the form of connection of the set by the one that better proved be obtained